PENGARUH PENGGUNAAN TEKNIK THINK TALK WRITE (TTW) BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS VII SMP NEGERI 11 PADANG - Fitri, Julia; Atmazaki, Atmazaki (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT  This purpose of this study is three. First, describing the procedure of writing text for students of class VII in Junior High School 11 Padang before using the Think Talk Write (TTW) technique by the media of serial images. Secondly, describing the procedure of writing text for students of class VII in Junior High School 11 Padang after using the TTW technique by the media of serial images. Third, analyzing the effect of the use of  TTW  techniqueby the media of serial images on the skills of writing procedure text for students of class VII in Junior High School 11 Padang. This type of research is quantitative research with one group pretest and posttest design experimental methods. There are three results of this study. First, the procedure of writing text in the seventh grade of Junior High School 11 Padang before using the TTW technique by the media of serial images is of good qualification (B) with an average value of 76,95 (under of minimal completeness criteria). Second, the procedure of writing text in the seventh grade of Junior High School 11 Padang after using the TTW technique by the media of serial images is of good qualification (B) with an average grade of 81,51 (above of minimal completeness criteria). Third, based on the t-test, H1 is accepted at the 95% confidence level and dk= (n1 as a numerator and n2 as denominator) because tcount>ttable (2,39>1,70).  Kata Kunci: Pengaruh, Teknik TTW, Media Gambar Berseri, Teks Prosedur